The effect of two types of stretching on flexibility in selected joints in youth soccer players - Andrea Mahrová; Pavel Hráský; František Zahálka; Petr Požárek (Palacký University Olomouc, 2014)
Background: The nature of soccer causes overloading of certain muscles and muscle groups that are most often involved in typical training activities of players. Often the absence of additional leisure-time activities typical for children and adolescents leads to an increased risk of muscle imbalance. Objective: We were interested in the occurrence of muscle imbalance, specifically an occurrence of muscle shortening and limited flexibility of the spine as well as decreased range of motion (ROM) in selected joints among young soccer players. Methods: The players were randomly selected to take part in the study. Twelve young soccer players took part in the first group and thirteen in the second group (age 13 years, body weight 40.5 ± 3.9 vs. 41.5 ± 7.8 kg, height 150.0 ± 5.0 vs. 153.0 ± 9.8 cm). The first team performed only static stretching exercises at the end of the training session and the other team performed, except for static stretching, also dynamic stretching exercises always at the beginning of the training session. The effect of the stretching program on range of motion in chosen joints was assessed by 2 × 2 repeated-measures ANOVA (stretching methods × time). The statistical significance of a-level was set to .05 and partial ηp2. Results: Pre-test measurements revealed an occurrence of muscle shortening and limited ROM of the spine and selected joints mostly in the pelvis and lower limbs in all study participants. Comparison of ROM in selected joints between pre-test and post-test in program including both static and dynamic stretching showed significant increase of left hip during flexion (p = .03, ηp2 = .20). The program with only static stretching showed significant decrease the ROM of ankle plantar flexion (p = .04, ηp2 = .18). We did not find any significant difference between stretching programs on ROM. As for muscle shortening, both side improvements (higher number of subjects with no muscle shortening) were found in the following muscle or muscle groups - m. trapesius, m. pectoralis major, m. rectus femoris, m. tensor fasciae latae, knee flexors and m. triceps surae. Improvements were also observed in group 1, but corrections were only asymmetrical. Conclusions: The stretching program in the group of soccer players could lead to increase of range of motion in some joints after a special program. It could serve as protection from muscle imbalance and lower limb injuries.